An Antifungal Role of Hydrogen Sulfide on Botryosphaeria Dothidea and Amino Acid Metabolism Involved in Disease Resistance Induced in Postharvest Kiwifruit - Duan, Bing; Du, Huaying; Zhang, Wei; Wang, Jing; Cai, Zhipeng; Shen, Yonggen; Huang, Tenghuan; Yuan, Jie; Gan, Zengyu; Chen, Jinyin; Zhu, Liqin (Frontiers in Plant Science, 2022)
Botryosphaeria dothidea is a major pathogen responsible for postharvest kiwifruit soft rot. This study aimed to determine the influence of hydrogen sulfide (H2S) on postharvest resistance to kiwifruit soft rot and the antifungal role of H2S against B. dothidea. The results indicated that H2S (20 μl L–1) restricted the lesion area following inoculation with B. dothidea. H2S enhanced the production of shikimic acid, tyrosine, tryptophan, and phenylalanine while also increasing total phenols, flavonoids, and lignin. H2S up-regulated the expression of AcDHQS, AcSDH, AcSK, AcPAL, AcCAD, and AcCHS. Additionally, sodium hydrosulfide (NaHS)-released H2S inhibited mycelial growth. NaHS concentrations of 20 and 40 mmol L–1 significantly decreased mycelial weight and MDA content while increasing cell membrane conductivity and membrane leakage. The results indicate that H2S induced resistance in kiwifruit via a microbicidal role and amino acid metabolism involved in postharvest kiwifruit disease resistance.